Advanced fibre-reinforced polymer (frp) composites for structural applications (Woodhead Publishing series in civil and structural engineering, 2013)
Advanced fibre-reinforced polymer (FRP) composites have become essential materials for the building of new structures and for the repair of existing infrastructure. This title provides an overview of different advanced FRP composites and the use of these materials in a variety of application areas.